The book of Psalms : composition and reception - Flint, Peter W.; Miller, Patrick D.; Brunell, Aaron.; Roberts, Ryan. (Vetus Testamentum, Supplements, 2005)
Written by leading experts in the field as well as some younger scholars, The Book of Psalms: Composition and Reception offers a wide-ranging treatment of the main aspects of Psalms study. The almost 30 essays consist of two overall sections. The first section contains studies of a more general nature; commentary on or interpretation of specific Psalms; social setting; and the Psalter as book. The second section contains essays on the literary context of the Psalter (including Qumran texts); textual history and reception in Judaism and Christianity; and the theology of the Psalter. The volume ends with a cumulative bibliography and several useful indices.